1994
DOI: 10.1128/jcm.32.11.2829-2831.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volume and periodicity on blood cultures

Abstract: Blood specimens collected for culture by using the high-volume resin-based BACTEC system over an 18-month period at the Seattle Veterans Administration Center were examined in this study. Of 7,783 cultures obtained, 624 were classified as true positives. Patients'in this group had between 20 and 60 ml of blood drawn per culture and separated into 10-ml aliquots for incubation. Analysis of the results stratified by cultured volume and time interval between specimen collection accorded yield advantage to culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
13

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(81 citation statements)
references
References 13 publications
(13 reference statements)
0
67
0
13
Order By: Relevance
“…This notion is based on many studies of patients with bacteraemia [4,[8][9][10][11][12]. Li et al demonstrated that increasing cultured volume from 20 to 40 mL increased yield by 19% [9]. Collecting only one BC should be discouraged because it results in an inadequate volume of cultured blood and therefore lacks sufficient sensitivity for detecting BSI [6].…”
Section: Introductionmentioning
confidence: 99%
“…This notion is based on many studies of patients with bacteraemia [4,[8][9][10][11][12]. Li et al demonstrated that increasing cultured volume from 20 to 40 mL increased yield by 19% [9]. Collecting only one BC should be discouraged because it results in an inadequate volume of cultured blood and therefore lacks sufficient sensitivity for detecting BSI [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since bacteria are rapidly cleared from blood and since fever spikes follow bacteremic episodes by 30 to 90 min, the best opportunity for recovering pathogenic microorganisms should be as soon after the fever spike as possible. Interestingly, in the only published systematic study of which we are aware, Li et al (97) showed that there was no difference in organism recovery between multiple blood cultures drawn simultaneously and those drawn serially over a 24-h period. Nonetheless, since blood cultures should be collected before antimicrobial agents are given and since newer blood culture systems can detect microbial growth within a few hours, it makes more sense to draw blood cultures simultaneously rather than serially.…”
Section: Diagnostic Strategies For Blood Culturesmentioning
confidence: 95%
“…This can be complicated for some freestanding dialysis centers that must send blood cultures out to sometimes distant laboratories. Third, blood cultures can yield false-negative results, especially if done after antimicrobials have been started or if inadequate volumes of blood are sampled (8,9). Blood cultures may also not detect some important pathogens (e.g., Legionella pneumophila) or results may be delayed when certain pathogens are involved (e.g., invasive fungal infections) (10).…”
Section: Advantages and Limitations Of Blood Culturesmentioning
confidence: 99%
“…To increase yield and to assist with interpretation, multiple culture sets should generally be obtained, but the recommended time interval between cultures varies. One study evaluated the timing of serial cultures and found no obvious difference in yield between cultures collected at the same time, 10 minutes to 2 hours apart, or 2 hours to 24 hours apart (9). CLSI recommends that blood cultures be drawn simultaneously or over a short interval (16).…”
Section: Timing and Yield Of Blood Culturesmentioning
confidence: 99%
See 1 more Smart Citation